Pengembangan Sistem Aplikasi Tanggap Bencana Banjir Berbasis SMS Gateway Menggunakan Mikrokontroler Berbasis Atmega328 Di Desa Kedawung Wetan Pasuruan - Sigit Riyadi; Kurniawan Wahyu Haryanto (SMATIKA JURNAL : STIKI Informatika Jurnal, 2020)
Kedawung Wetan village is one of the areas in Pasuruan district that often receives floods due to overflow from the Rejoso River. The river overflow was caused by water sent from higher ground areas south of Kedawung Wetan Village, namely Lumbang Village and Winongan Village. Due to the flood disaster, many residents were unable to save their belongings because floods could occur at any time. In Kedawung Wetan village, early warning of floods is still running manually, which still involves humans in providing information so that errors can occur. In addition, the Kedawung Wetan village still covers 2G networks, so an application that can work on 2G networks is needed. To overcome this, in this study, it was found that the village of Kedawung Wetan needed an early warning technology based on an SMS Gateway which could operate on a 2G network, input that runs automatically using a device based on the AtMega 328 Arduino microcontroller which is equipped with an ultrasonic sensor as a water level detector. streams and SIM 900 GSM Shield for sending SMS alerts. The research development was carried out using the Waterfall method. The development of this system shows that the average time for sending messages is 2 minutes, the fastest time is 1.5 minutes and the longest time is 2.5 minutes using 3 different sample operators.